2000
DOI: 10.1088/0954-0083/12/3/306
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Containing Polyesterimides

Abstract: New silicon-containing polyesterimides have been synthesized by a solution polycondensation reaction, in a high-boiling-point solvent, of a silicon-containing diacid chloride (namely bis(p-chlorocarbonyl-phenylene)-diphenylsilane) with certain dihydroxy-compounds having preformed imide rings. All these polymers were soluble in polar amidic solvents, such as N-methylpyrrolidinone and dimethylformamide, and gave thin transparent films on casting their solutions. The polymers exhibited high thermal stability, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…1). All acid dichlorides obtained decompose when they are distilled over 80 ºC (2)(3)(4)(5) approximately. For this reason, characterization and polymerization were developed from the crude portion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). All acid dichlorides obtained decompose when they are distilled over 80 ºC (2)(3)(4)(5) approximately. For this reason, characterization and polymerization were developed from the crude portion.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of silane links such as -SiR 1 R 2 -in the main chain, improve the solubility and increase the glass transition temperature in front of wholly aromatic polymers. M. Bruma has described several kinds of Si-containing condensation polymers with different functional groups and studied their properties [2][3][4][5][6]. Also, the lower electronegativity of the Si atom with respect to the C one would imply an increase of the thermal stability due to an ionic character of the C-Si bond when compared with the C-C ones, in spite of the similar bond energy dissociation of both bond [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…2,[10][11][12][13] Likewise, it has been reported the preparation of polycondensation materials that include the ester and other functional groups. 4,6,14 On the other hand, Migdal et al 15 reported the synthesis of a series of dimethylsilylen-containing aliphatic poly(esters). These polymers are based on the reactions of bis(p-carboxymethylphenyl) dimethylsilane diacid and the dialcohols bis(p-hydroxymethylphenyl) dimethylsilane and bis(p-b-hydroxyethylphenyl)dimethylsilane.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible to find structures based on bis(p-hydroxyphenylene) [7][8][9][10][11][12][13] , bis(pbromophenylene) 14 , bis(aminophenylene)meta and para isomers, 10,14-16 and bis(p-carboxyphenylene) 11,17,18 , bis(p-ch orocarbonylphenylene) 11,[17][18][19][20][21] , bis(pcarboxyalkylphenylene) 20,22 , bis(p-(3,4 dicarboxyphenylene)) dianhydride 16,[23][24][25][26] , bis(p-isocyanatephenylene) 27 , bis(p-carbohydrazidophenylene) 22 , bis(p acidazidephenylene) 14 and bis(p-chloroformatephenylene) 13,28 moieties. The several polymers obtained from these aromatic monomers show low chain-mobility with low to moderate glass transition temperatures (Tg).…”
Section: Introductionmentioning
confidence: 99%